Re-Imagining Child and Youth Care Practice with African Canadian Youth - Daniel, Beverly-Jean; Jean-Pierre, Johanne (International Journal of Child, Youth and Family Studies, 2020)
This article is based on a plenary held during the Child & Youth Care in Action VI Conference: Moving Through Trails and Trials Toward Community Wellness, held in Victoria, British Columbia in April 2019. It explores how we can re-imagine child and youth care practice with African Canadian youth. This emerging paradigm aligns with child and youth care politicized praxis as well as trauma-informed and strengths-based approaches in the field’s literature. We highlight the importance of mobilizing critical and transformative theoretical frameworks along with an Africentric worldview to substantially support youth of African descent with a strengths-based approach. Moreover, the protective role of Black-affirming spaces is developed and articulated.